Prevention of peritonitis in newly-placed peritoneal dialysis catheters: efficacy of oral prophylaxis with cefuroxime axetil - a preliminary study - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2016)
BACKGROUND: Peritonitis is one of the causes of early peritoneal dialysis (PD) failure in newly-placed catheters. Antibiotic prophylaxis has been recommended to decrease the risk of infection after PD catheter placement. In this study, we compared the efficacy of parenteral versus oral prophylactic cefuroxime axetil for preventing peritonitis after placed PD catheters. METHODS: In total, 67 patients (F/M: 32/35; mean age: 46.6 +/- 13.2 years) undergoing 70 percutaneous PD catheter placement procedures were included (in three patients, placement was repeated). In 37 patients (parenteral group), we administered a single intravenous (IV) 750-mg dose of cefuroxime axetil, approximately 30 min before placement. In the oral group, 33 patients received a 500-mg dose of oral cefuroxime axetil 1 hour before the procedure and the patients continued that twice daily for 3 days. Patients were evaluated for peritonitis over the following 14 days. The costs of both oral and parenteral forms of cefuroxime axetil were calculated. RESULTS: The two groups were similar regarding age and gender. Three patients (9%) in the oral group and three (8.1%) in the parenteral group developed peritonitis (P=0.578). All were responded to therapy for peritonitis. The cost of parenteral prophylaxis was $US 7.58, while that of the oral form was $US 3.92. CONCLUSION: For patients undergoing percutaneous PD catheter insertion, a 3-day regimen of oral cefuroxime axetil for preventing early peritonitis was safe, equally effective, and had lower cost comparing with single intravenous dose of the same agent.
Keywords: Antibiotic prophylaxis; Catheter; Peritoneal dialysis; Peritonitis; Cefuroxime axetil; VANCOMYCIN-RESISTANT ENTEROCOCCI; SURGICAL SITE INFECTION; ANTIMICROBIAL PROPHYLAXIS; ANTIBIOTIC-PROPHYLAXIS; SURGERY; STATEMENT; INSERTION